[OP.1C.01] INCREASED BLOOD PRESSURE VARIABILITY PREDICTS ALL-CAUSE MORTALITY IN PATIENTS WITH DIABETES FREE OF CARDIOVASCULAR DISEASE AND NOT ON ANTIHYPERTENSIVE DRUGS. (September 2017) - Nilsson, P.; Bell, K.; Azizi, L.; Hayen, A.; Irwig, L.; Östgren, C.; Sundström, J.
Abstract : Objective: Blood pressure variability has been associated with risk of cardiovascular events in observational studies, independently of mean blood pressure (BP) levels. BP variability is typically summarized as the standard deviation (SD), coefficient of variation (CV), or variation independent of mean (VIM), of blood pressure over multiple office blood pressure readings, days apart. Design and method: Using data from a Swedish primary health care cohort of patients with diabetes, we identified 12, 179 patients (2, 321 with and 9, 858 without pre-existing cardiovascular disease, CVD), who had at least two BP measurements within the first year, did not change BP-lowering treatment during the observation period, and had >0 for calculated variability measures. Patients were followed for a median of four years. Associations of variability measures (SD, CV, VIM) with mortality, adjusting for other risk factors (Framingham Risk Score variables - including mean BP, HbA1c, insulin treatment), were investigated using Cox proportional hazards models. Results: BP variability was not associated with mortality in the total sample after adjusting for Framingham Risk Score variables +/− other significant variables. However, in patients without CVD who were not on BP-lowering drugs (n = 2, 949), variability measures were statistically associated with mortality, with adjusted hazard ratios (HRs) of 1.29 (95% confidence interval 1.02–1.62), 1.27 (0.97–1.53) and 1.28 (1.01–1.62) for SD, CV and VIM, respectively. Estimates were similar but with wider confidence intervals, when allowance was made for competing causes of mortality. Importantly, addition of the variability measures led to very minimal improvement in discrimination, indicating they may have limited clinical usefulness (change in C-statistic ranged from 0.000–0.002 in all models). Conclusions: Although BP variability was statistically associated with all-cause mortality in diabetes patients in primary care who did not have pre-existing CVD or BP-lowering drugs, it may be of minimal clinical usefulness above and beyond that of other routinely measured predictors. Early control of mean BP level may be more important than reduction of BP variability in patients with diabetes.